في تعزيز إتقان المفردات اللغوية لدى طلاب الصف الثاني في منطقة جوفينج بولاية بيراق Ezy-Flash Mufrodat فاعلية استخدام تطبيق: The Effectiveness of Using the Ezy-Flash Mufrodat Application in Enhancing Vocabulary Mastery among Second-Year Students in Gopeng, Perak - Azmi, Nur Ardiani (SIBAWAYH Arabic Language and Education, 2024)
تعد المفردات العنصر الأكثر أهمية في تعلم اللغة العربية، حيث تعتبر أساسًا لتطوير مهارات اللغة المختلفة مثل التحدث والكتابة. ومع ذلك، يواجه العديد من الطلاب تحديات في إتقان المفردات العربية وتذكرها على نحو فعّال. للتغلب على هذه التحديات، اعتمدت المعلمة تطبيق Ezy-Flash Mufrodat كنشاط تعليمي يهدف إلى تعزيز إتقان الطلاب للمفردات العربية. تهدف هذه الدراسة إلى تحسين ذاكرة الطلاب للمفردات العربية من خلال توظيف الطريقة البصرية (المرئية)، وزيادة دافع الطلاب نحو تعلم المفردات من خلال استخدام نشاط Ezy-Flash Mufrodat ، وأخيرا تطوير مهارات الطلاب في التحدث والكتابة عبر المشاركة في أنشطة هذا التطبيق. شملت عينة الدراسة 30 طالبًا من الصف الثاني من إحدى المدارس في منطقة جوفينج، ولاية بيراق. اعتمدت الدراسة على المنهج شبه التجريبي، مستخدمةً اختبارًا قبليًا وبعديًا كأداة لقياس فعالية التطبيق. أظهرت نتائج الدراسة أن تطبيق Ezy-Flash Mufrodat ساهم بشكل فعّال في تحسين ذاكرة الطلاب للمفردات العربية، كما أظهر الطلاب تحسنًا في مهارات التحدث والكتابة نتيجة مشاركتهم في أنشطة هذا التطبيق. تبيّن من النتائج أن استخدام Ezy-Flash Mufrodat يُعد وسيلة فعّالة لتعزيز إتقان المفردات العربية لدى الطلاب، مما يعزز من تجربتهم التعليمية ويزيد من تحفيزهم.Vocabulary is the most crucial element in learning Arabic, as it forms the basis for developing various language skills, such as speaking and writing. However, many students face challenges in effectively mastering and remembering Arabic vocabulary. To address these challenges, the teacher adopted the Ezy-Flash Mufrodat application as an educational activity aimed at enhancing students' vocabulary mastery. This study aims to improve students' memory of Arabic vocabulary by employing a visual approach, increase students' motivation to learn vocabulary through the use of the Ezy-Flash Mufrodat activity, and develop students' speaking and writing skills through participation in this application's activities. The study sample consisted of 30 second-year students from a school in Gua Musang, Perak. The study adopted a quasi-experimental methodology, using pre- and post-tests as tools to measure the application's effectiveness. The results showed that the Ezy-Flash Mufrodat application effectively contributed to improving students' memory of Arabic vocabulary. Moreover, students demonstrated improvement in speaking and writing skills as a result of their participation in the activities. The results indicate that using Ezy-Flash Mufrodat is an effective means to enhance students' mastery of Arabic vocabulary, thereby enriching their learning experience and boosting their motivation.Keywords: Vocabulary, Arabic Language, Ezy-Flash Mufrodat, Students' Memory, Speaking Skill, Writing Skill.